Urban canyon effect: storm drains enhance call characteristics of the Mientien tree frog. (5th June 2014) - Tan, W.‐H.; Tsai, C.‐G.; Lin, C.; Lin, Y. K.
Abstract Anthropogenic structures, such as wall surfaces, may change the acoustic environment for signals transmitted by animals, creating novel environments that animals must either adapt to or abandon. Animals can potentially use those structures to manipulate sound characteristics. In many anuran species, successful reproduction depends on long‐range propagation and perception of advertisement calls. Callers may select natural perches or human‐made objects to assist call propagation. Male Mientien tree frogs Kurixalus idiootocus frequently perch and call in roadside concrete drainages – miniature urban canyons. We used a combination of field and indoor experiments to test two hypotheses: (1) transmission of calls emitted inside drains is enhanced; (2) males selected perches inside drains that facilitated call transmission. A field survey indicated that male Mientien tree frogs preferred calling inside rather than outside drains. A playback showed that calls emitted from inside drains were enhanced in both amplitude and note duration. In an indoor experiment using a replica of a concrete drain, males preferred one particular type of call perch. However, we found no difference in sound properties between random locations inside the drain model and the perch location preferred by calling males.